2010
DOI: 10.1007/s10526-010-9289-7
|View full text |Cite
|
Sign up to set email alerts
|

Late blight on potato is suppressed by the biosurfactant-producing strain Pseudomonas koreensis 2.74 and its biosurfactant

Abstract: Potato late blight disease caused by the zoospore-producing pathogen Phytophthora infestans (Mont.) de Bary is one of the most destructive plant diseases world-wide and currently its management mainly relies on the frequent use of fungicides. This study investigated the possibility of reducing potato late blight by biocontrol with the biosurfactantproducing strain Pseudomonas koreensis 2.74. Significant disease reduction with the biosurfactantproducing strain and its biosurfactant was observed in greenhouse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…The presence of similar constituent analogues in both the rhamnolipids highlights their key role in the results obtained in the microtitre assay against C. falcatum spore germination. Hultberg et al reported that no reduction in mycelial growth rate of Phytophthora infestans was observed for the biosurfactant produced by Pseudomonas koreensis 2.74 at concentrations of 50, 100, and 200 μg ml −1 . Only at the highest concentration (1000 μg ml −1 ), significant reduction in growth rate was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of similar constituent analogues in both the rhamnolipids highlights their key role in the results obtained in the microtitre assay against C. falcatum spore germination. Hultberg et al reported that no reduction in mycelial growth rate of Phytophthora infestans was observed for the biosurfactant produced by Pseudomonas koreensis 2.74 at concentrations of 50, 100, and 200 μg ml −1 . Only at the highest concentration (1000 μg ml −1 ), significant reduction in growth rate was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as pointed out by Hultberg et al (11), the use of nonpathogenic microorganisms is a fundamental and essential issue for biological control. Among Pseudomonas , 23 and 16 species have been shown to exhibit pathogenicity against plants and animals (including humans), respectively (10).…”
Section: Discussionmentioning
confidence: 99%
“…It too exhibited antagonistic activities: a biosurfactant was active both against Phytium ultimum in a tomato model system (21) and against Phytophthora infestans infecting potato plants (22). Another P. koreensis strain, CRS05-R05, was isolated from the rice rhizosphere and showed biocontrol activity against the rice weevil Sitophilus oryzae (23), a pest of stored foods.…”
Section: Introductionmentioning
confidence: 99%